Analisis Konsumsi Arus Operasional Blok Kontrol dan Regulasi Tegangan pada Cascaded DC-DC Boost Converter sebagai Catu Daya Elektrostimulator Terapi Medis - Ivana Tawaru; Devi Yuliani Seran; Agung Nugraha Rahman; Eko Arianto (PT Bukuloka Literasi Bangsa, 2026)
This study aims to analyze the voltage regulation and control current consumption characteristics of a two-stage Cascaded DC-DC Boost Converter (5 V to 12 V, and 12 V to 97 V) utilized as a power supply for medical therapy electrostimulators. The experimental method was conducted by integrating the power supply block with an active load configuration consisting of a Voltage Controlled Current Source (VCCS) circuit. Testing was performed by varying the therapy current from 2 mA to 10 mA at a frequency of 100 Hz across three variations of simulated patient tissue resistance (470 Ω, 560 Ω, and 1 kΩ). The experimental results indicate that the open-loop cascaded power supply system undergoes a static voltage drop of 24.32% from the ideal regulation (97 VDC to 73.4 VDC) due to internal parasitic losses and initial loading of the control circuit. Nevertheless, this 73.4 VDC voltage amplitude exhibits robust horizontal stability without secondary fluctuations throughout the dynamic loading range (2 mA to 10 mA), thereby providing sufficient voltage headroom to ensure precise current regulation linearity in the VCCS block without waveform clipping. The value of this research lies in providing an empirical analysis of open-loop cascaded power supply regulation characteristics in maintaining accurate therapy current dosages for portable medical instrumentation. Keywords: Cascaded Boost Converter, Electrostimulator, Voltage Regulation, VCCS Linearity